Improving fermentative hydrogen and methane production from an algal bloom through hydrothermal/steam acid pretreatment. (1st March 2019) - Cheng, Jun; Yue, Liangchen; Ding, Lingkan; Li, Yu-You; Ye, Qing; Zhou, Junhu; Cen, Kefa; Lin, Richen
Abstract: Algal blooms can be harvested as renewable biomass waste for gaseous biofuel production. However, the rigid cell structure of raw algae may hinder efficient microbial conversion for production of biohydrogen and biomethane. To improve the energy conversion efficiency, biomass from an algal bloom in Dianchi Lake was subjected to a hydrothermal/steam acid pretreatment prior to sequential dark hydrogen fermentation and anaerobic digestion. Results from X-ray diffraction and Fourier transform infrared spectroscopy suggest that hydrothermal acid pretreatment leads to stronger damage of the amorphous structure (including hemicellulose and amorphous cellulose) due to the acid pretreatment, as evidenced by the higher crystallinity index. Scanning electron microscopy analysis showed that smaller fragments (∼5 mm) and wider cell gaps (∼1 μm) on algal cell surfaces occurred after pretreatment. In comparison to steam acid pretreatment, hydrothermal acid pretreatment resulted in a maximum energy conversion efficiency of 44.1% as well as production of 24.96 mL H2 /g total volatile solids (TVS) and 299.88 mL CH4 /g TVS. Highlights: Algal bloom from Dianchi Lake was pretreated by hydrothermal/steam acid. The microstructural changes before and after pretreatment were comparatively revealed. Hydrothermal acid led to the highest H2 yield (25.0 mL/g) and CH4 yield (299.9 mL/g). Hydrothermal acid led to the highest energy conversion efficiency of 44.1%.